PENGARUH VARIASI DAYA DAN LAMA WAKTU KONTAK LAMPU ULTRAVIOLET TIPE C PADA LEMARI STERILISASI TERHADAP PENURUNAN JUMLAH KUMAN PADA ALAT MAKAN DI KANTIN OFFICE PT.X - Irmawartini, Irmawartini; Kusmawati, Elma Dwi; Djuhriah, Nany (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
The problem of food sanitation hygiene was very important to be addressed, especially in food management facilities such as office canteens. It was found that the number of germs on cutlery in the PT X canteen exceeded the established quality standard, namely 150 colonies/cm2. Attempts to reduce the number of germs on the cutlery of dishes by sterilization using UV-C light. This study aims to determine the variation in power and the length of contact time of ultraviolet lamp type C (UV-C)  using a sterilization cabinet against reducing the number of germs on the cutlery at PT.X This type of research is an experiment with a posttest with control design. The cutlery used as a sample was 25 pieces. Data analysis was bivariate statistic analysis.  Based on the results, it was known that there was a decrease in the number of germs after UV-C light irradiation was carried out. Irradiation with a power of 15 watts long contact 25 minutes lowers the number of germs 96.89%, Irradiation with a power of 15 watts long contact 30 minutes lowers the number of germs 98.65%, Irradiation with a power of 30 watts long contact 25 minutes lowers the number of germs 99.89%, and Irradiation with a power of 30 watts long contact 30 minutes decreases the number of germs 100%. A decrease in the number of effective germs occurs at a lamp power of 30 watts with a time contact duration of 30 minutes.